Quantitative genetic variation in growth, cold tolerance and wood density of Corymbia citriodora subsp. variegata and Corymbia torelliana in Argentina - Gimenez, Carla Anahí; Lopez, Juan Adolfo; Vera Bravo, Carlos David; Harrand, Leonel; Martinez Meier, Alejandro (Springer, 2025)
In this study, growth traits, cold tolerance and basic wood density genetic variation of 55 families of Corymbia citriodora subsp. variegata (CCV) and 40 families of C. torelliana (CT), were evaluated in a taxa/origin trial in Concordia, Entre Rios, Argentina. Height (TH), diameter at breast height (DBH), the latter two used for individual volume (V), frost tolerance (FROST) and basic wood density (WD) were assessed at 2 years old of age. Narrow-sense heritability for growth traits (TH and DBH) ranged from 0.22 to 0.19 and 0.45 to 0.51 for CCV and for CT, respectively. For FROST, were 0.34 for CCV and 0.38 for CT, indicating moderate magnitude of additive genetic control in this trait. Trait-trait genetic correlations between growth traits were positive and high, and between V and FROST, values were favorable and moderate to high, ranging from − 0.42 and − 0.65. For WD, genetic correlations between all traits were not statistically significant, indicating an independency or weak association. In addition, it was possible to select promising individuals through their predicted additive genetic values and individual gain, in order to rank them hierarchically to those individuals that combine performance, cold tolerance and wood density, which will be used or the continuity of the Corymbia´s breeding strategy in Argentina.